EDUKASI PEMBERDAYAAN MASYARAKAT PEMENUHAH KEBUTUHAN CAIRAN DAN ELEKTROLIT GUNA MENCEGAH DEHIDRASI - Suroso, Heri; Qomariah, Siti Nur; Bakar, Abu; Paraswati, Mareta Deka (Community Development in Health Journal, 2025)
Introduction & Aim: Fluid balance in the body is one of the important aspects of the physiology of the human body related to homeostasis, if the human body does not have a fluid balance, it will experience dehydration, which will affect its health. Dehydration is a condition when there is an imbalance of fluids in the body, usually caused by fluid loss due to exposure to high temperatures for a long period of time. The purpose of this community service is to provide fulfilment of fluid and electrolyte needs to prevent dehydration. Method of Activity: Fluid balance in the body is one of the important aspects of the physiology of the human body related to homeostasis, if the human body does not have a fluid balance, it will experience dehydration so that there is a community service activity in the form of community empowerment. The activity begins with providing information to increase community understanding about fulfilling fluid and electrolyte needs to prevent dehydration. Indirect assistance, by utilising whatsapp group facilities. The level of success of community service is carried out by observing initial knowledge and preparedness and comparing knowledge and preparedness after community service activities. Data were analysed with the Wilcoxon Signed Rank Test.mpak on their health. Dehydration is a condition when there is an imbalance of fluids in the body, usually caused by fluid loss due to exposure to high temperatures for a long period of time. The purpose of this community service is to provide fulfilment of fluid and electrolyte needs to prevent dehydration. Results: The preparedness of community members before education with 15 participants was 20% (3 people) had a high level of preparedness, 53.3% (8 people) had a medium level of preparedness, and 26.7% (4 people) had a low level of preparedness. While preparedness after education as many as 80% (12 people) have a moderate level of preparedness and 20% (3 people) have a high level of preparedness. there are 6 people have an increase in preparedness after education and 9 people have the same level of preparedness so that there is an effect of education with changes in community preparedness (p = 0.027). Discussion: Community service highlights the importance of the role of health workers in improving patient preparedness through counselling and providing appropriate information.